Em busca de vozes perdidas: Lênio Braga, muralismo, "arquivo" e comunicação oral - Silva, Andréa do Nascimento Mascarenhas (2009)
The ideas that shape the pursuit of doctoral walk two parallel directions: 1) the living presence of objects in the oral traditions of culture, indicated by the maximum reflection of the Africa "every time an old man who dies is a library burning," motto of the project and that maximizes the sense of what I call "archives" of orality, 2) recognition of media able to capture the voice of the text and giving oral to listen / communicate matters apparently "immaterial." Generally, in an attempt to "see" the voice through the image, try to understanding the coming to be more different "archives" of orality, its scope and configurations plastic: material spaces almost invisible to the unsuspecting eye, sometimes hidden in the collective and individual memories, sometimes materialized in mechanical records (such as burning, shooting, etc virtual spaces.) or artistic creations. And in this study the fine arts make an example of such communicative reading to be possible on an "archive" from the mouth. Looking then study the muralist of plastic Lênio Braga. I want to emphasize the potential of "archives" moving, unconventional (and) that can record, to "pass" and deal with the presence of voice in multiple media. The corpus of the analysis is composed of digital photos of three murals installed in stations road of the Bahia: Jequié, Itabuna and Feira de Santana, which were created by the artist in the 1960s. The wall is justified by the interest in this approach, by considering them "media" art or other "archives" of the orality. Can establish connections: the popular imagination and swing stories typical to each local municipality in which the murals are in establishing and activating 'hypertexts'. The direction of the research seeks to understand the "passage" of oral communication for the image and the image for voice, continually. The vectors that theoretical concepts guiding the study are as 'sensitive listening' and 'culture as a memory '(by Claude Filteau and Jerusa Pires Ferreira), records of imagination (by Marlyse Meyer) 'movência' (by Paul Zumthor); 'cultural transfer' - which includes the idea of intermedialidade (by Walter Moser); 'shift translation and mestizo' culture (by José Lezama Lima and José Amálio Pinheiro Branco). Since the murals are of Lênio Braga as "texts" of culture and memory - areas of communication and interaction of orality/voice detected in the image - note the communicative aspect of greater interest as a field of work. The methodology was based on qualitative/participative research, field research (partially), researches biographical and bibliographical; included the steps of criticism, "reading" / analysis of the images and communicative plan had the support of the theories above